2018
DOI: 10.7196/samj.2018.v108i3.12627
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the burden of cervical disease among HIV-infected women accessing screening services in South Africa: A model-based analysis

Abstract: Background. Cervical cancer remains the second most common cancer among women worldwide, with much of the global burden occurring in low-and middle-income countries. HIV-infected women are at increased risk of human papillomavirus infection, preinvasive cervical disease and invasive cervical cancer (ICC). Funded through the United States President's Emergency Plan for AIDS Relief (PEPFAR) and working in collaboration with the South African (SA) Department of Health, our team supports cervical screening integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…One of the study sites was a hospital‐based clinic co‐located with a large public‐sector HIV treatment program, which provides cervical cancer screening and treatment of precancerous lesions to approximately 3000 women infected with HIV annually. The second site was a mobile clinic, which provides screening services to 2000 women in one of Johannesburg's poorest townships each year …”
Section: Methodsmentioning
confidence: 99%
“…One of the study sites was a hospital‐based clinic co‐located with a large public‐sector HIV treatment program, which provides cervical cancer screening and treatment of precancerous lesions to approximately 3000 women infected with HIV annually. The second site was a mobile clinic, which provides screening services to 2000 women in one of Johannesburg's poorest townships each year …”
Section: Methodsmentioning
confidence: 99%
“…South Africa has the highest age-standardised incidence of cervical cancer globally, with 32 cases per 100,000 women (22), whereas Paraguay (a middle-income country) has the highest incidence (34.2 per 100,000 women) and a mortality rate of 15.7 per 100,000 women (21,23). These results indicated that women infected with HIV may be at a higher risk of developing HPV infection, pre-invasive cervical disease and invasive cervical cancer (ICC) (18,24,25). Currently, South Africa has the highest incidence of HIV infection worldwide, with ~7.2 million cases in a population of 58 million (26); an estimated 13 million women are infected with HIV in sub-Saharan Africa (25,27).…”
Section: Cervical Cancer Incidence In Low-to Middle-income Countriesmentioning
confidence: 99%
“…The natural history of cervical cancer has been studied, and it has been concluded that the persistent infection of the cervix by the oncogenic types of Human papillomavirus (HPV 16 & HPV 18) is the necessary cause in 72% of cervical cancers in Africa [ 11 , 31 ]. South Africa is reported to be home to the largest number of HIV-infected individuals, with nearly 60% of incident HIV infections occurring in women [ 32 - 34 ]. Previously performed systematic reviews and analysis have showed that the overall risk of HIV acquisition in women doubled when they had a prevalent HPV infection with any genotype, and that HIV acquisition was significantly associated with any HPV infection [ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%